Suatu Tinjauan Mengenai Brainware Management - Bram Hadianto; Safruddin Harahap; Nuryamin Budi (Jurnal Manajemen Maranatha, 2007)
Organization needs a person who has learning culture over period of time, especially in business. To achieve this objective, every person must understand the learning process in their brain and emotion. Brainware management provides facilities for this purpose. Through managing human brain and emotion, organization can compete effectively in the business.